Is the German energy transition perceived as gender- and socially-just? - Marika Kuschan; Uta Burghard; Kiara Groneweg; Annika Strebel (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2022)
[Conclusion] The aim of this paper was to investigate citizens' perceptions of the energy transition initiated by the federal government through the lens of gender and social justice. For this purpose, data were collected in surveys and workshops with two target groups - TG 1 comprising persons already ac-tively participating in the energy transition, and TG 2 made up of persons who have not been active in the energy transition so far. As already elaborated, there are no crucial differences in the perceptions of these two target groups. One main result was that the energy transition planned by the German government, i.e. in a top-down approach is perceived as generally unjust by both groups. It is noteworthy that gender as-pects were not seen as the main drivers of this injustice. Instead, the participants pointed out that specific social groups are not yet considered enough when it comes to energy transition projects. Practical recommendations for the federal government can be derived from the results of this study: The federal government should include an intersectional perspective in their energy policies as well as in acceptance policies and measures. This should increase the approval of energy transition pro-jects by German citizens in terms of accessibility, use of energy services, investments or decision-making processes. To ensure a gender-just and socially-just energy transition, different perspectives must be included, since all social groups influence the energy value chain (in households, local communities, and energy markets). The participation and representation of different social groups must be encouraged and planned, not only from the governmental side, but also from the civil society side. As mentioned in the dis-cussion, citizen energy projects in Europe are still dominated by white men with financial resources. Diversifying and democratizing citizen energy projects requires acceptance at local level, i.e. at community level, as a precondition. Once citizens are convinced about the potential of such energy projects and mobilised to take part, such citizen energy projects have huge potential to influence energy policies from the bottom up. Recent developments, such as the war in Ukraine, can be regarded as an additional driver to in-crease the acceptance of renewable energy projects. The resulting rising prices and predicted short-ages for fossil fuel-based energy could lead to a stronger shift towards renewable energies. Fur-thermore, the war has enhanced the awareness in society of the dangers of dependency on energy/ fossil fuels from abroad. This could act as another driver towards locally produced renewable ener-gies and their increased acceptance by society.
Keywords: 330